Pengaruh Metode Struktural Analitik Sintetik (SAS) Berbantuan Media Audio Visual Terhadap Keterampilan Membaca dan Menulis Siswa Sekolah Dasar - Alamsah, Dwiki; Arif, Tarman A.; Haslinda, Haslinda (Universitas Cokroaminoto Palopo, 2023)
This study discusses the effect of the synthetic structural analytic method (SAS) assisted by audio-visual media on students' reading and writing skills. This study aims to determine whether there is an effect of the synthetic Structural Analytical method assisted by audio-visual media on students' reading and writing skills. The type of research used is Quasi Experimental Design with the Nonequivalent Control Group Design type. The population in this study were all class I Cluster III Galesong District consisting of six schools with a total of 332 students. The sample in this study was class I students at SDN No. 190 Inpres Bura'ne, totaling 53 people using cluster random sampling technique. Data collection techniques in this study were carried out through technical tests to determine students' initial reading and writing skills in the form of questions and reading texts. The results of the study are based on the Independent Sample T Test Hypothesis 1, decision-making framework, if the significance value is less than 0.05, it can be said that the synthetic structural analytic method (SAS) assisted by audio-visual media on beginning reading skills. The significance value obtained from the independent sample t test is 0.00, which is smaller than 0.05. Therefore, it can be stated that there is an influence of the synthetic structural analytic method (SAS) assisted by audio-visual media on beginning reading skills. At the same time, the Independent Sample T Test Hypothesis 2 findings show that the significance value for the test is 0.00, which is less than 0.05. Consequently, it is possible to say that there is an influence of the synthetic structural analytic method (SAS) assisted by audio-visual media on initial writing skills. And the results of the Manova test, the significance value obtained from the Manova test is 0.00, which is smaller than 0.05. Therefore, it can be stated that there is an influence of the synthetic structural analytic method (SAS) assisted by audio-visual media on initial reading and writing skills